无料钟布料装置传动系统中行星差动减速器的设计 - 石加联; 刘明伟; 陈东 (Jixie chuandong)
When non-bell distributor operates,horizontal rotation and chute tilting cooperate with each other,several distribution patterns such as circular,fan-shaped,rotary and fixed-point distribution are realized.Distributing effect is directly influenced by the design of distributor transmission system,which in turn influences the production of the blast furnace.The planetary differential reducer is an important part of the transmission system,which has the advantages of large transmission ratio,strong bearing capacity,compact structure,extensive adaptability,etc.Planet differential reducer is designed and analyzed through reasonable selection and analysis of the transmission form,the control of rotation and tilting movement is realized by means of the differential between the main and side motor,and finally the accurate and reliable distribution of the blast furnace is realized.